Contemporary voices [compact disc] - Murphy, Otis; Ran, Shulamit, 1949-; Higdon, Jennifer, 1962-; Zwilich, Ellen Taaffe, 1939- (Cedille, 2020)
The Grammy Award-winning Pacifica Quartet performs works by three Pulitzer Prize-winning contemporary composers: Shulamit Ran, Jennifer Higdon, and Ellen Taaffe Zwilich.